Capacity Building of Health Professionals on Genetics and Genomics Practice: Evaluation of the Effectiveness of a Distance Learning Training Course for Italian Physicians - Calabrò, Giovanna Elisa; Tognetto, Alessia; Mazzaccara, Alfonso; Barbina, Donatella; Carbone, Pietro; Guerrera, Debora; Di Pucchio, Alessandra; Federici, Antonio; Ricciardi, Walter; Boccia, Stefania (Frontiers in Genetics, 2021)
Background. The rapid spread of personalized medicine requires professionals to manage the “omics revolution”. Therefore, the genetics/genomics literacy of healthcare professionals should be in line with the continuous advances in this field, in order to implement its potential implications for diagnosis, control and treatment of diseases. The present study investigates the effectiveness of a distance learning course on genetics and genomics targeted at medical doctors. Methods. In the context of a project funded by the Italian Ministry of Health, we developed a distance learning course, entitled Genetics and Genomics practice. The course focused on genetic/genomics testing, pharmacogenetics and oncogenomics and was developed according to andragogical training methods (Problem-based Learning and Case-based Learning). We used a pre-test versus post-test study design to assess knowledge improvement on a set of 10 Multiple Choice Questions (MCQs). We analysed the proportion of correct answers for each question pre and post-test and the mean score difference stratified by gender, age, professional status and medical discipline. Moreover, the test was submitted to the participants eight months after the conclusion of the course (follow-up), in order to assess the retained knowledge. Results. The course was completed by 1637 Italian physicians, most of which were primary care physicians (20.8%), public health professionals (11.5%) and specialist pediatricians (10.6%). The proportion of correct answers increased in the post-test for all the MCQs. The overall mean score significantly increased, from 59.46 in the pre-test to 71.42 in the post-test (p-value<0.0001). The comparison in test performance between follow-up and pre-test demonstrated an overall knowledge improvement. Conclusions. Genomics literacy among healthcare professionals is essential to ensure optimal translation to healthcare delivery of research. The results of this course suggest that distance-learning training in genetic/genomics practice represents an effective method to improve physicians’ knowledge in the immediate and mid-term time scale. A preprint version of this paper is available at: https://www.researchsquare.com/article/rs-10083/v1